UMAT AGAMA DALAM PAGUYUBAN NGESTI TUNGGAL (PANGESTU) (Religious Members Paguyuban Ngesti Tunggal (Pangestu) ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Paguyuban Ngesti Tunggal (Pangestu) is one of the Javanese mysticism groups that was established as a formal organization in Solo in 1949 inÂ¬spired by a 'revelation' to Soenarto Mertowardojo (Pakde Narto). Based on the movement doctrine rooted on Kitab Sasangka ]ati, Pangestu is not a reliÂ¬gion and does not establish a new religion. Pakde Narto and his fellows also refuse Pangestu as an association of mysticism (Himpunan Penganut Kepercayaan (HPK)). They prefer to call Pangestu as 'Faculty of Psychology', a place for mental spiritual forging. As the consequence of that doctrine, Pangestu is not only followed by them who declare themselves as abangan but also by those who obey their religion (Moslem or Christian). To Pangestu doctrine, its followers can be described as people who have tolerance and vision to other religious followers. Anthropologically, the participation of the followers of the religions to Pangestu becomes a unique problem. Because of that, they have enclosed two belief systems